Elementary Education in Uttrakhand: An Appraisal - Sharma, Sandeep Kumar; Rani, Manju; Sharma, Ravendra (JOURNAL OF INDIAN EDUCATION, 2010)
The article 45 of Indian constitution has provision of free and compulsory education for all children upto the age of 14 years. Systematic and planned efforts were made by Government to achieve and fulfill this commitment. In the year 1986 a new education policy was adopted and efforts were made through successive five year plans to achieve the target of 100 % literacy through compulsory and free education for the children of age group 6-14. After the District Primary Education Programme (DPEP) of 1994, the govt. has now launched the “Sarva Shiksha Abhiyan” or SSA in 2001 to universalise and improve the quality of elementary education in India through community ownership of elementary education. However, even after sixty two years of India’s independence the goal of universal elementary education has not been achieved so far. About 10 million children of school going age are not attending elementary schools due to various reasons. This paper discusses the scenario of elementary education in Uttrakhand keeping in view the Government efforts for universalising the elementary education. The data for this paper are accumulated from different sources such as 7th All India School Education Survey 2002, survey conducted by NCERT, and State Report Cards prepared by NUEPA, Delhi etc. Educational parameter at district level are discussed and analysed to draw the attention of researchers, policy makers, administrators, and educationist for achieving the target of SSA in the State.